Reference pricing with elastic demand for pharmaceuticals - Gonçalves, Ricardo (2016)
This paper analyzes pharmaceutical producers (of branded and generic drugs) pricing de- cisions in a context which combines the classical Hotelling framework (commonly adopted in the literature) with the possibility that consumers demands are price elastic. We analyze with particular interest two commonly adopted reimbursement mechanisms: xed percentage reim- bursement (FPR) and reference pricing (RP). We nd that assuming an elastic demand has a signi cant impact under a RP mechanism, as it allows rms to raise their prices when the copayment rate increases. Contrary to previous literature, we show that RP may be worse than FPR in terms of social welfare for su¢ ciently high copayment rates. From a policy viewpoint, our results indicate that the introduction of RP is not necessarily always bene cial (compared to FPR) and thus constitute a model towards which all reimbursement mechanisms should converge.